Induction of endoplasmic reticulum stress and unfolded protein response constitutes a pathogenic strategy of group A streptococcus - Baruch, Moshe; Hertzog, Baruch B.; Ravins, Miriam; Anand, Aparna; Catherine Youting, Cheng; Biswas, Debabrata; Tirosh, Boaz; Hanski, Emanuel (Frontiers in Cellular and Infection Microbiology, 2014)
The connection between bacterial pathogens and unfolded protein response (UPR) is poorly explored. In this review we highlight the evidence showing that group A streptococcus (GAS) induces endoplasmic reticulum (ER) stress and UPR through which it captures the amino acid asparagine (ASN) from the host. GAS acts extracellularly and during adherence to host cells it delivers the hemolysin toxins; streptolysin O (SLO) and streptolysin S (SLS). By poorly understood pathways, these toxins trigger UPR leading to the induction of the transcriptional regulator ATF4 and consequently to the upregulation of asparagine synthetase (ASNS) transcription leading to production and release of ASN. GAS senses ASN and alters gene expression profile accordingly, and increases the rate of multiplication. We suggest that induction of UPR by GAS and by other bacterial pathogens represent means through which bacterial pathogens gain nutrients from the host, obviating the need to become internalized or inflict irreversible cell damage.